Galaxy And Mass Assembly (GAMA): Structural Investigation of Galaxies via Model Analysis - Kelvin, L; Driver, S; Robotham, A; Hill, D; Alpaslan, M; Baldry, I; Bamford, S; Bland-Hawthorn, J; Brough, S; Graham, A; Häussler, B; Hopkins, A; et al. (2012)
We present single-Sérsic two-dimensional (2D) model fits to 167600 galaxies modelled independently in the ugrizYJHK bandpasses using reprocessed Sloan Digital Sky Survey Data Release Seven (SDSS DR7) and UKIRT Infrared Deep Sky Survey Large Area Survey imaging data available from the Galaxy And Mass Assembly (GAMA) data base. In order to facilitate this study we developed Structural Investigation of Galaxies via Model Analysis (sigma), an r wrapper around several contemporary astronomy software packages including source extractor, psf extractor and galfit 3. sigma produces realistic 2D model fits to galaxies, employing automatic adaptive background subtraction and empirical point spread function measurements on the fly for each galaxy in GAMA. Using these results, we define a common coverage area across the three GAMA regions containing 138269 galaxies. We provide Sérsic magnitudes truncated at 10r e which show good agreement with SDSS Petrosian and GAMA photometry for low Sérsic index systems (n < 4), and much improved photometry for high Sérsic index systems (n > 4), recovering as much as Δm= 0.5mag in the r band. We employ a K-band Sérsic index/u-r colour relation to delineate the massive (n > ~2) early-type galaxies (ETGs) from the late-type galaxies (LTGs). The mean Sérsic index of these ETGs shows a smooth variation with wavelength, increasing by 30 per cent from g through K. LTGs exhibit a more extreme change in Sérsic index, increasing by 52 per cent across the same range. In addition, ETGs and LTGs exhibit a 38 and 25 per cent decrease, respectively, in half-light radius from g through K. These trends are shown to arise due to the effects of dust attenuation and stellar population/metallicity gradients within galaxy populations. © 2012 The Authors Monthly Notices of the Royal Astronomical Society © 2012 RAS.